NEXT-GENERATION GENE SEQUENCING AND ITS APPLICATIONS IN ONCOHEMATOLOGY - I. M. Barkhatov; A. V. Predeus; A. B. Chukhlovin (Онкогематология, 2017)
The review bears on basic principles and technologies of next-generation sequencing (NGS), as well as its applications for detection of gene mutations in leukemic cells. We discuss some novel data concerning NGS approach to studies of genetic heterogeneity in myeloproliferative disorders, detection of high-risk genes, including drug resistance mutations, epigenomic changes associated with leukemias, as well as molecular aspects of clonal evolution. A special section concerns basic problems with bioinformatics and adequate analysis of large digital databases obtained with NGS approach. Optimal choice of appropriate software is of utmost importance for adequate retrieval and interpretation of the NGS data.